Sulfidogenesis in pretreatment of high-sulfate acidic wastewater using anaerobic sequencing batch reactor and upflow anaerobic sludge blanket reactor - Chaiprapat S. (2014)
In rubber skim block production, use of sulfuric acid is a general practice, which generates acidic wastewater (pH 2.4±0.5) with high chemical oxygen demand (COD) (14,911±1,819mg/L) and sulfate (6,506±1,038mg/L). Our work aimed to pretreat this wastewater separately prior to combining with the other wastewaters to facilitate efficient anaerobic digesters that follow. Results indicated that sulfate removal efficiency of the anaerobic sequencing batch reactor (ASBR) pretreating raw rubber skim wastewater (pH 2.43±0.50) was only 7.25%±4.01% and gradually improved with increasing influent pH to 45.45%±3.75% at pH 7. In the second part, upflow anaerobic sludge blanket (UASB) and ASBR fed with the rubber skim wastewater at pH 7 faced system failure after 97 days of operation. When the influent pH was adjusted to 8, sulfate removals of UASB and ASBR at 27.37%±2.55% and 46.58%±1.98%, respectively, could be sustained. A distinctive ASBR operation that allows mixing and settling phases was deemed as key to enable, respectively, better substrate dispersion and retention of the poor granulating sulfate-reducing bacteria. © 2011, Mary Ann Liebert, Inc.